UPACARA AGAMA HINDU DI BALI DALAM PERSPEKTIF PENDIDIKAN KONSERVASI TUMBUHAN. ( SUATU KAJIAN PUSTAKA) - I Dewa Putu Darma (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2008)
ABSTRACT The activity of Hindus religion in Bali is based on the philosophy of Tri Hita Karana. The used of the “banten” in the ceremony can`t loose from plants. In general most of the Hindus people in Bali can make and do this ceremony but they don`t understand what the purpose of the ceremony is. The Tumpek pengatag, Nangluk merana, Tibe baya, Ngentegang woh pepayonan ceremonies and it`s conection of the rice in the rice field as strategy component in conservation plants of education in Bali. Whereas the function of the plants ceremonies that remembering the human being to take care of the plants, so the ceremony can be continuously.